Effects of аntimicrobials on Pseudomonas aeruginosa biofilm formation - U. M. Nemchenko; K. O. Sitnikova; N. L. Belkova; E. V. Grigorova; N. M. Voropaeva; M. V. Sukhоreva; E. S. Sukhareva; E. D. Savilov (Вавиловский журнал генетики и селекции)
Pseudomonas aeruginosa is one of the most problematic pathogens in medical institutions, which may be due to the ability of this microorganism to exist in a biofilm, which increases its resistance to antimicrobials, as well as its prevalence and survival ability in the external environment. This work aimed to evaluate the antimicrobial susceptibility of P. aeruginosa strains in planktonic and biofilm forms. We studied 20 strains of P. aeruginosa collected during 2018–2021 by specialists from the Laboratory of Microbiome and Microecology of the Scientific Centre for Family Health and Human Reproduction Problems. The identification of strains was carried out using test systems for differentiating gram-negative non-fermenting bacteria (NEFERMtest 24 Erba Lachema s.r.o., Czech Republic), and confirmed by mass spectrometric analysis and 16S rRNA gene sequencing. Antimicrobial activity was assessed by the degree of inhibition of cell growth in planktonic and biofilm forms (on a flat-bottomed 96-well plastic immunological plate). All clinical isolates of P. aeruginosa were biofilm formers, 47.6 % of the isolates were weak biofilm formers, and 52.4 % of the isolates were moderate biofilm formers. Planktonic cells and the forming biofilm of the tested P. aeruginosa strains were carbapenems-resistant. Biofilm formation was suppressed in more than 90 % of cases by the agents of the cephalosporin and aminoglycoside groups. Antimicrobial susceptibility of P. aeruginosa strains in the formed biofilm was significantly lower (p < 0.05). Carbapenems and cephalosporins did not affect the mature biofilms of the tested P. aeruginosa strains in more than 60 % of cases. Only non-beta-lactam antibiotics (ciprofloxacin and amikacin) suppressed the growth of planktonic cells and destroyed the mature biofilm. The revealed differences in the effect of the tested antimicrobials on the P. aeruginosa strains biofilms correlate with resistance to a number of antibiotics. To prevent biofilm formation in the hospital strains of P. aeruginosa, the use of ceftazidime may be recommended, and antimicrobials such as ciprofloxacin and amikacin may be used to affect mature biofilms of P. aeruginosa.